EFFECTIVENESS, BENEFITS, EASE OF USE, AND SECURITY ON INTEREST IN USING E-MONEY: EXPERIENCES DURING THE PANDEMIC - ningrum, eny puspita (JURNAL SOCIUS, 2024)
The use of e-money in the era of technological advancement is highly effective for transactions. However, the utilization of e-money as a digital payment tool still requires further study to maximize its benefits. This research aims to determine the significance of the effectiveness of e-money usage on community interest in Desa Takisung during the pandemic.The study employs a quantitative method with a descriptive research design. Information was collected from respondents using questionnaires measured on an ordinal scale in the form of a Likert scale. The research sample consists of residents of Desa Takisung, with the criteria of being at least 20 years old and e-money users. Data sources include primary and secondary sources. Primary data were obtained through questionnaires distributed to 100 respondents, while secondary data were collected from books and journals.The results indicate that perceptions of usefulness, ease of use, and security positively and significantly influence interest in using e-money during the pandemic.